2011
DOI: 10.1242/dmm.006262
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Mks1 localization to the mother centriole causes cilia defects and developmental malformations in Meckel-Gruber syndrome

Abstract: SUMMARYMeckel-Gruber syndrome (MKS) is a recessive disorder resulting in multiple birth defects that are associated with mutations affecting ciliogenesis. We recovered a mouse mutant with a mutation in the Mks1 gene (Mks1del64-323) that caused a 260-amino-acid deletion spanning nine amino acids in the B9 domain, a protein motif with unknown function conserved in two other basal body proteins. We showed that, in wild-type cells, Mks1 was localized to the mother centriole from which the cilium was generated. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 73 publications
3
58
0
Order By: Relevance
“…Bbs4 -/- mutant embryos exhibit normal neural patterning (Fig 1J). Previous studies examining the phenotypes of Mks1 mutant embryos report complex neural patterning phenotypes wherein cell types that require intermediate levels of SHH for their patterning are slightly expanded, with the ventral most cells including V3 interneurons slightly reduced in number in more caudal regions of the neural tube [39,48]. We similarly observed only a slight expansion of OLIG2+ motor neuron progenitors at the forelimb level in Mks1 single mutants (Fig 1K).…”
Section: Resultssupporting
confidence: 69%
“…Bbs4 -/- mutant embryos exhibit normal neural patterning (Fig 1J). Previous studies examining the phenotypes of Mks1 mutant embryos report complex neural patterning phenotypes wherein cell types that require intermediate levels of SHH for their patterning are slightly expanded, with the ventral most cells including V3 interneurons slightly reduced in number in more caudal regions of the neural tube [39,48]. We similarly observed only a slight expansion of OLIG2+ motor neuron progenitors at the forelimb level in Mks1 single mutants (Fig 1K).…”
Section: Resultssupporting
confidence: 69%
“…Particularly notable is their phenotypic similarity to Mks1 mutant mice that are models of MKS [27],[28]. This included anophthalmia (Figure 1A), central polydactyly (Figure 1B,C), and cysts in the kidney and a variety of other organs (Figure 1D,E).…”
Section: Resultsmentioning
confidence: 91%
“…For example, two independent studies identified recessive mutations in Mks1, and showed that loss of this gene impacted the assembly of functional cilia. Moreover, these mouse mutants had phenotypes similar to those seen in human Meckel Syndrome, Type 1 (Cui et al, 2011; Norris and Grimes, 2012; Weatherbee et al, 2009), including craniofacial defects, and the mutation in the Mks1 krc allele was also detected at an equivalent position in MKS1 for an affected human patient (Norris and Grimes, 2012). Similarly, the ENU-induced Cauli phenotype, which results in missing or reduced facial cartilage and bone among other defects, is caused by a mutation in Ift40 (Miller et al, 2013).…”
Section: Introductionmentioning
confidence: 67%